Meant to be mine - Orenstein, Hannah (Atria Paperback, 2022)
"What if you knew exactly when you'd meet the love of your life? Edie Meyer knows. When her Grandma Gloria was a young woman, she had a vision of the exact day she would meet the love of her life - and then Grandpa Ray showed up. Since then, Gloria has accurately predicted the day every single member of the family has met their match. Edie's day is Friday, June 24, 2022. That morning, she boards an airplane to fly to her twin sister Rae's engagement. When a handsome stranger takes a seat in her row, she knows her whole life is about to change. But fate is more complicated than it seems, and her perfect guy may not be so perfect for her after all. After tragedy and a shocking revelation rock Edie's careful world, she has to ask which is more important: fate or love?"--